Turismo e arquitetura contemporânea: a produção de meios de hospedagem em Fortaleza-Ce - Rocha, Carlos Bruno Oliveira (2024)
Highlighting the role of tourism in the urbanization of the Metropolitan Region of Fortaleza, it can be seen that social practices to increase tourist activity in the region through the actions of the State, expressed in public policies, and tourist, hotel and real estate capital, are related to contemporary architectural production, resulting in the construction of a variety of categories of lodging facilities. In view of this, the general aim of this work is to carry out a formal and functional typological analysis of four contemporary buildings of the Fortaleza waterfront lodging facilities built since the 1980s as case studies: the Hotel Gran Marquise (1986), the Iate Plaza (1997), the Blue Tree Towers Fortaleza (1997) and the Landscape (2008). The theoretical assumptions of the methodology are based on the discussion of tourism and tourist urbanization in Fortaleza and the metropolitan region; the concepts of type and language in contemporary architecture; as well as the relationship between the production of accommodation facilities and real estate capita. The practical assumptions refer to the typological analysis of the case studies. Finally, this research aims to contribute to the advancement of knowledge about the relationship between tourism and contemporary architecture, namely about the production of lodging facilities in the city of Fortaleza, through documentation, digital modeling, and typological analysis of the works.